TJNPR 2022
DOI: 10.26538/tjnpr/v6i7.1
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Alpha Lipoic Acid to Maintain Liver Function Tests in XenobioticInduced Liver Toxicity: A Narrative Review

Abstract: benefits including a protect effect on the liver. The present review is an up-to-date paper of current thinking regarding ALA and its use in providing antioxidant drug therapy on the potential role of ALA on xenobiotic-induced liver injury. Chemistry of ALALA is also called thioctic acid and is chemically named 1,2-dithiolane-3-pentanoic acid (C8H14O2S2): with an oxidized (disulfide, LA) and a reduced (di-thiol: dihydro-lipoic acid, (Fig. 1) DHLA) form of LA. 6 Figure 1: Chemical structures of lipoic acid (LA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 124 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Overall, the evidence suggests that Tempol has the ability to restore normal liver function in mice with APAP-induced acute hepatotoxicity by activating the PI3K/Akt/Nrf2 pathway, thereby enhancing the antioxidant response and inhibiting hepatic apoptosis. Studies have provided evidence that lipoic acid exhibits a potential therapeutic benefit in treating the liver structural and chemical aberrations instigated by an overdose of the analgesic drug APAP in male albino mice (Tiiba et al, 2022). Besides, studies have revealed that lipoic acid possesses the ability to prevent APAP-induced liver damage by reducing necrosis, inflammation, and oxidative stress in the liver and promoting liver regeneration.…”
Section: Histopathologymentioning
confidence: 99%
“…Overall, the evidence suggests that Tempol has the ability to restore normal liver function in mice with APAP-induced acute hepatotoxicity by activating the PI3K/Akt/Nrf2 pathway, thereby enhancing the antioxidant response and inhibiting hepatic apoptosis. Studies have provided evidence that lipoic acid exhibits a potential therapeutic benefit in treating the liver structural and chemical aberrations instigated by an overdose of the analgesic drug APAP in male albino mice (Tiiba et al, 2022). Besides, studies have revealed that lipoic acid possesses the ability to prevent APAP-induced liver damage by reducing necrosis, inflammation, and oxidative stress in the liver and promoting liver regeneration.…”
Section: Histopathologymentioning
confidence: 99%